2016
DOI: 10.1186/s12864-016-3249-2
|View full text |Cite
|
Sign up to set email alerts
|

A MAGIC population-based genome-wide association study reveals functional association of GhRBB1_A07 gene with superior fiber quality in cotton

Abstract: BackgroundCotton supplies a great majority of natural fiber for the global textile industry. The negative correlation between yield and fiber quality has hindered breeders’ ability to improve these traits simultaneously. A multi-parent advanced generation inter-cross (MAGIC) population developed through random-mating of multiple diverse parents has the ability to break this negative correlation. Genotyping-by-sequencing (GBS) is a method that can rapidly identify and genotype a large number of single nucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 62 publications
1
85
0
Order By: Relevance
“…However, the extremely unbalanced parental compositions might dilute the GWAS efficiency (Xiao et al ., ). To thoroughly intercross and effectively balance the contributions of all founder lines, the advanced generation intercross (MAGIC) populations of rice were established in various species (Kover et al ., ; Huang et al ., ; Bandillo et al ., ; Dell'Acqua et al ., ; Islam et al ., ). The application of NAM or MAGIC populations is largely limited, due to the requirement for extensive field and laboratory effort.…”
Section: The Development Of Gwasmentioning
confidence: 97%
“…However, the extremely unbalanced parental compositions might dilute the GWAS efficiency (Xiao et al ., ). To thoroughly intercross and effectively balance the contributions of all founder lines, the advanced generation intercross (MAGIC) populations of rice were established in various species (Kover et al ., ; Huang et al ., ; Bandillo et al ., ; Dell'Acqua et al ., ; Islam et al ., ). The application of NAM or MAGIC populations is largely limited, due to the requirement for extensive field and laboratory effort.…”
Section: The Development Of Gwasmentioning
confidence: 97%
“…Most of the mapping studies in sugarcane have used traditional molecular markers such as simple sequence repeat (SSR), restriction fragment length polymorphism (RFLP), amplified fragment length polymorphism (AFLP), random amplified polymorphic (RAPD) and diversity array technology (DArT). With the advent of next‐generation sequencing (NGS) technologies and appropriate bioinformatics software, genotype by sequencing (GBS), as a restriction enzyme‐based method, has been proven to be efficient in rapidly identifying and genotyping large numbers of single‐nucleotide polymorphism (SNP) markers in many crops both diploid (Elshire et al., ; Pace, Gardner, Romay, Ganapathysubramanian, & Lubberstedt, ; Vuong et al., ) and polyploid (Islam, Thyssen, Jenkins, & Fang, ; Islam et al., ; Poland, Brown, Sorrells, & Jannink, ). However, the GBS technology has rarely been exploited in sugarcane genotyping due to its highly heterozygosity, large genome size and lack of reference genome to facilitate downstream SNP analysis.…”
Section: Introductionmentioning
confidence: 99%
“…MLMs have been widely used as they consider population structure and kinship, which would ultimately control the false association to a greater extent. Many association mapping studies published to date were dedicated to study seed quality (Badigannavar & Myers, ), yield (Kantartzi & Stewart, ), fibre quality (Abdurakhmonov et al., ; Islam et al., ), maturity (Su et al., ) and biotic (Zhao, Wang, Chen, & Li, ) and abiotic stress tolerance (Saeed, Wangzhen, & Tianzhen, ; Yin‐hua et al., ) traits. We report here population structure, kinship and an average extent of genomewide LD for cotton germplasm using 23,254 informative markers from a total of 63,058 SNP markers screened.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of mapping studies reported so far in cotton are based on SSRs (simple sequence repeat markers; Nie et al, 2016). To date, very few SNP-based genomewide association studies are reported in cotton (Islam et al, 2016;Su et al, 2016). Recently, 63K SNP-chip has been developed by Hulse-Kemp et al (2015) in cotton.…”
Section: Introductionmentioning
confidence: 99%